Advantages Of Using Information Technologies In Primary Grades - Uljalgas Abdullayeva (Euro Asian Journal Publishing, 2024)
This article highlights the advantages and conveniences of using information and communication technologies, that is, modern computer technologies, in primary school classes
Keywords: primary education; information; computer; technology